Schematic and realistic model calculations of the isovector spin monopole excitations in 116In - Bes,Daniel Raúl (2012)
The excitation of Gamow-Teller (GT) and isovector spin monopole (IVSM) Jπ=1+ modes in 116In by (p,n) and (n,p) charge-exchange reactions on 116Cd and on 116Sn, respectively, is studied within the framework of the quasiparticle random-phase approximation. The calculations have been performed both for schematic and realistic model situations. It appears that the calculated admixture of the IVSM and Gamow-Teller (GT) Jπ=1+ excitations is negligible and that the contribution to the strength above 20 MeV of excitation energy, in 116In, is due to the IVSM (σr2t ±) mode. This result is compared with the recent experimental work that reported a large amount of both (p,n) and (n,p) strength beyond 10 MeV of excitation energy in 116In. This measured excess strength has led to speculations about its importance for the double beta decay rate of 116Cd.